Medicarpin confers powdery mildew resistance in Medicago truncatula and activates the salicylic acid signalling pathway. (8th March 2022) - Gupta, Arunima; Awasthi, Pallavi; Sharma, Neha; Parveen, Sajiya; Vats, Ravi P.; Singh, Nirpendra; Kumar, Yashwant; Goel, Atul; Chandran, Divya
Abstract: Powdery mildew (PM) caused by the obligate biotrophic fungal pathogen Erysiphe pisi is an economically important disease of legumes. Legumes are rich in isoflavonoids, a class of secondary metabolites whose role in PM resistance is ambiguous. Here we show that the pterocarpan medicarpin accumulates at fungal infection sites, as analysed by fluorescein‐tagged medicarpin, and provides penetration and post‐penetration resistance against E. pisi in Medicago truncatula in part through the activation of the salicylic acid (SA) signalling pathway. Comparative gene expression and metabolite analyses revealed an early induction of isoflavonoid biosynthesis and accumulation of the defence phytohormones SA and jasmonic acid (JA) in the highly resistant M. truncatula genotype A17 but not in moderately susceptible R108 in response to PM infection. Pretreatment of R108 leaves with medicarpin increased SA levels, SA‐associated gene expression, and accumulation of hydrogen peroxide at PM infection sites, and reduced fungal penetration and colony formation. Strong parallels in the levels of medicarpin and SA, but not JA, were observed on medicarpin/SA treatment pre‐ or post‐PM infection. Collectively, our results suggest that medicarpin and SA may act in concert to restrict E. pisi growth, providing new insights into the metabolic and signalling pathways required for PM resistance in legumes. Abstract : Infection‐localized accumulation of the isoflavonoid phytoalexin medicarpin provides resistance against the pea powdery mildew pathogen and activates salicylic acid signalling in Medicago truncatula .